Valuation of the cooperativa multiactiva coomercap to make decisions - Sáenz Córdoba, Jairo; Riascos Araujo , Andrés Darío (SATHIRI, 2022)
The purpose of this research was to try to identify the value of "COOMERCAP" located in the city of Pasto (Col), so that at the end, it responds to the concerns raised in the general objectives which is to determine the value of the cooperative and the specific objectives among which are stated; to diagnose the financial situation of the company on the basis of the five basic financial statements, to apply the methods defined by the literature of financial management for the assessment, to identify the weak points from the results and to design strategies that improve and correct the failure. The research offers the opportunity to get to know if the cooperative has proved creation or destruction of value, because the growth must be justified and be sustainable in the long term in a manner that ensures the development of new projects of expansion and growth with the penetration of new markets locally and internationally. Taking into account that the assessment of companies has no major studies applied to cooperatives in the region of Pasto, the evaluation of the companies in the cooperative can provide knowledge. The benefits received by the interest groups that the organization has such as; to have the necessary information to value the company in the stock  market, to know the equity of the company, and the management of managers, to set a dividend policy, and  restructure the capital, to know the level of indebtedness, among others, thus contribute to enterprise development.
Keywords: Financial Statements; Company; Financial Management; Equity; Indebtedness